From Babel to biosemiotics: Christine Brooke-Rose's Joycean scripts. Issue 8 (3rd August 2022) - Smith, Gabriel
ABSTRACT: In one of her least pejorative references to Joyce, Christine Brooke-Rose cites him as an example of a writer who shares with philologists a 'dotty' passion for the history of language. Coming in the middle of her students' guide to Ezra Pound, this claim assigns linguistic sentiments to Joyce that Brooke-Rose would go on to express herself. In an interview nearly five years later, she describes a 'passionate concern with language' that borders on 'the feeling of the sacred': 'I've always had it. I studied philology'. This essay unearths a vein of Joycean philological imaginings in Brooke-Rose's work that seeks to intertwine the textual and the biological, evoking a 'sensuous' script from a mythical prehistory. Focusing on Between (1968), I trace an intricate ambivalence over the relationship between sign and matter that ultimately feeds into Brooke-Rose's attitudes towards poststructuralism, gender, and language as a whole. Hovering between the sacred and the profane, the dotty and the down-to-earth, these imaginings also serve to draw out the latent continuities between the ancient hunt for a motivated script and the contemporary search for semiosis in nature; between Babel and biosemiotics.